Organizational world-class level in the continuous improvement process: case study in automotive organizations - Ferraz, Thais Cristina Pereira; de Souza, Luiz Gonzaga Mariano; Mello, Carlos Henrique Pereira (Revista Gestão da Produção Operações e Sistemas, 2007)
This paper presents a discussion on the aspects related to the efficiency and the efficacy of the continuous improvement management. The proposal of the paper is to present such practice as a technology that superpasses the limits of the normative fulfillment of the quality management systems. For this reason, this paper based on the xx multiple case study – having as empirical elements of investigation – car enterprises from the southern region of the state of Minas Gerais, Brazil. From the description of the investigated organizations, which characterize the levels of organizational excellence regarding continuous improvement, it is discussed the sustentation and the evolution of the continuous improvement concept, made feasible by the organizational learning process. The study points out xx the need to articulate the training and educational activities xx as well, which are relevant in the development and maturation in the management of this technology. It xx emphasizes, therefore, the relevance of the integration between the social and technical systems as a base for the continuous improvement, by means of the perfection and potentiation of the abilities which define the level of its excellence. Keywords: Continuous improvement; Quality; Maturity.